2021
DOI: 10.1136/heartjnl-2020-318787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medical treatment on heart failure incidence in patients with a systemic right ventricle

Abstract: BackgroundTo date, clinical trials have been underpowered to demonstrate a benefit from ACE inhibitors (ACEis) or angiotensin II receptor blockers (ARBs) in preventing systemic right ventricle (sRV) failure and disease progression in patients with transposition of the great arteries (TGA). This observational study aimed to estimate the effect of ACEi and ARB on heart failure (HF) incidence and mortality in a large population of patients with an sRV.MethodsData on all patients with an sRV under active follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Drugs available for systemic LV failure are usually used to treat patients with sRV failure, with largely disappointing results. For example, current data do not support using β-blockers, ACEis, ARBs, or aldosterone receptor antagonists in cc-TGA or d-TGA patients (19,(87)(88)(89)(90)(91)(92)(93)(94)(95). Dos et al recently reported that 14 sRV patients treated with the aldosterone-receptor antagonist eplerenone showed reduced collagen turnover biomarkers, but whether this correlated with an improvement in sRV function could not be determined (87).…”
Section: Medical Therapymentioning
confidence: 90%
“…Drugs available for systemic LV failure are usually used to treat patients with sRV failure, with largely disappointing results. For example, current data do not support using β-blockers, ACEis, ARBs, or aldosterone receptor antagonists in cc-TGA or d-TGA patients (19,(87)(88)(89)(90)(91)(92)(93)(94)(95). Dos et al recently reported that 14 sRV patients treated with the aldosterone-receptor antagonist eplerenone showed reduced collagen turnover biomarkers, but whether this correlated with an improvement in sRV function could not be determined (87).…”
Section: Medical Therapymentioning
confidence: 90%
“…Indeed, depending on the risk of HF, these patients may benefit from regular monitoring, cardiac rehabilitation programs, early detection and treatment of supraventricular rhythm disorders, and early HF treatment when the patient starts to be symptomatic 27 . Although medical therapy has failed to show preventive efficacy on heart failure events and death in several studies, screening of high risk patients will, maybe, allow to show some benefit in this cohort in future studies 7,8 . However, the present score models evaluate a composite endpoint, and predictors may vary according to the event assessed, even if several factors overlap the risk of HF and sudden cardiac death in patients with a sRV.…”
Section: Discussionmentioning
confidence: 99%
“…No patients were implanted with a ventricular assist device as destination therapy. Causes of death were HF (7), sudden cardiac death (4), non-cardiac death (2) and unknown (2). Median event-free survival of event-naive patients surviving into adulthood was 50 years (95% CI 48-52), and median survival until death or heart transplantation of adults with TGA after atrial switch was 53years (95% CI 51-54).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Such a design appears unrealistic. However, using a different approach, we demonstrated in a retrospective observational cohort including 359 patients with an sRV the lack of significant association between renin-angiotensin-aldosterone system inhibitors and a reduced HF incidence or mortality [22].…”
Section: Systemic Right Ventricle Failurementioning
confidence: 92%
“…Data from prospective controlled studies are scarce and valuable but can be considered as underpowered. Based on HF prevalence in patients with an sRV who did not receive ARBs after a median follow-up of 8.3 years in van Dissel et al study [21], we estimated that 199 patients would be required to be enrolled in each study group to achieve 80% power at the 5% significance level (two-sided) to detect an absolute reduction of 10% over a 7-year follow-up (i.e., 20% in the control group and 10% in the treated group) [22]. Such a design appears unrealistic.…”
Section: Systemic Right Ventricle Failurementioning
confidence: 99%